THE EFFECT OF PHYSICAL ACTIVITY ON C-REACTIVE PROTEIN (CRP) LEVEL AMONG OBESE POST MENOPAUSAL WOMEN - Faustina Theresa; Nila Wahyuni (Sport and Fitness Journal, 2023)
The results of the study show that the menopausal transition is associated with increased fat and inflammation, which are at risk for cardiovascular disease. Physical activity is recommended as an effective approach to reducing and preventing risk. The method used is a systematic literature review with Proquest database, Google Scholar, national and international journals with year range from 2012 - 2023. The criteria for the articles were female research subjects, young or old, obese with a BMI > 30 kg/m2 , with post menopausal conditions. The results showed that physical activity can reduce CRP levels. Given the importance of establishing physical activity in reducing CRP levels, this article aims to assess the effect of physical exercise on inflammatory biomarkers as a predictor of cardiovascular disease (CRP) in postmenopausal women with obesity, then further explore the potential role of C-reactive protein in this association. Keywords: physical activity, obesity , menopause, CRP